2016
DOI: 10.1186/s12917-015-0629-9
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever virus transmission cycles in Central Europe: Evaluation of wild boar-soft tick contacts through detection of antibodies against Ornithodoros erraticus saliva antigen

Abstract: BackgroundAfrican swine fever (ASF) is one of the most complex viral diseases affecting both domestic and wild pigs. It is caused by ASF virus (ASFV), the only DNA virus which can be efficiently transmitted by an arthropod vector, soft ticks of the genus Ornithodoros. These ticks can be part of ASFV-transmission cycles, and in Europe, O. erraticus was shown to be responsible for long-term maintenance of ASFV in Spain and Portugal. In 2014, the disease has been reintroduced into the European Union, affecting do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
160
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(169 citation statements)
references
References 16 publications
6
160
2
1
Order By: Relevance
“…While previous studies in horses have found that repeat injections of allogeneic MSCs do not cause overt clinical symptoms of transplant rejection [15,16], these studies did not thoroughly investigate whether a cell-mediated or humoral immune response was induced or whether this limited the persistence of the cells in vivo. As the likely therapeutic benefits of MSCs appear to be largely due to the secretion of paracrine factors that promote healing of healthy tissue [30,31], it is necessary for the cells to persist throughout the initial inflammatory and healing period.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies in horses have found that repeat injections of allogeneic MSCs do not cause overt clinical symptoms of transplant rejection [15,16], these studies did not thoroughly investigate whether a cell-mediated or humoral immune response was induced or whether this limited the persistence of the cells in vivo. As the likely therapeutic benefits of MSCs appear to be largely due to the secretion of paracrine factors that promote healing of healthy tissue [30,31], it is necessary for the cells to persist throughout the initial inflammatory and healing period.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge on the occurrence of these ticks in other areas of Europe is rather incomplete. However, in the Baltic countries, in Poland and in Central Europe their presence seems unlikely, as their involvement in the epidemiological cycle of the disease [29]. Such ticks are able to retain ASFV for a long time, at least 5 years, and to transmit it to susceptible species [30, 31].…”
Section: Reviewmentioning
confidence: 99%
“…While in diabetes, the adipose tissue secretes cytokines into the serum, cell and clinical work suggest a modulatory role of FFAs on cytokine levels; addition of fatty acids to cultured cells is reported to increase levels of IL-6, IL-8, IL-18, IL-β, pro-matrix metalloproteinase-1 (MMP-1) and pro-MMP3 while decreasing levels of IL-10, IL-12, interferon gamma (IFNγ) and CCL2 [102], [103], [104], [105] and [106]. Further, insulin-induced inhibition of FFA release reduces levels of IL-18, but not of IL-6 or TNFα [107].…”
Section: Lipid Metabolism Post-burnmentioning
confidence: 99%